(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the effects of different placement timings of definitive coronal restorations on endodontically treated teeth (ETT) and analysis of other factors resulting in extraction of such teeth. Study Design: Retrospective study. Place and Duration of Study: This study was conducted at the College of Dentistry, Qassim University, Saudi Arabia from May 2012 to January 2018. Materials and Methods: Data of 4,012 patients who received endodontic treatment and final coronal restorations were gathered from dental records. Reasons and time of extraction of ETT were noted. Results: significant association was found between extraction of ETT and female gender (p < 0.00) and 60+ days waiting time of final coronal restoration (p < 0.00). Year of dental students and number of visits of RCT did not have significant association with extraction of ETT (p = .366 and .654 respectively). Conclusion: Final coronal restorations should be placed within first two weeks after completion of RCT. This reduces the risk of extraction of ETT.